Ligatures and their leib-bound and socially mediated leib-bound ties – foundations for an actualization of Ralf Dahrendorf’s concept of life chances with recourse to Karl Popper’s theory of the three worlds and its extension - Leonardi, Laura; Kühne, Olaf; Berr, Karsten (SocietàMutamentoPolitica, 2025)
This essay deals with the extension of two concepts that have proven themselves in social science research and philosophy, but also have the potential to be applied in other contexts on the one hand, and to enter into a reciprocal connection on the other, namely Ralf Dahrendorf’s life chances approach and Karl Popper’s theory of three worlds. The extension of the Three Worlds Theory concerns the intersubjective, that of the life chances approach the integration of the human leib (as a connection between body and mind) into the concept of ligatures (which, in conjunction with options, form and determine life chances). The leib not only shapes ligatures, but it also mediates social ligatures, so that it has a prominent influence on life chances.